2010
DOI: 10.1159/000280438
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorocarbon Improves Post-Transplant Survival and Early Kidney Function following Prolonged Cold Ischemia

Abstract: Background: The two-layer organ preservation method (TLM) based on oxygenated perfluorocarbon overlaid with University of Wisconsin (UW) solution has been successfully used in clinical islet and experimental heart and intestine transplantation. We tested whether this technique would prevent tissue damage and improve kidney function in a model of syngeneic kidney transplantation with prolonged ischemia time. Methods: Kidneys were stored for 24 h either in UW solution (n = 16), with TLM (n = 16) or transplanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Artificial oxygen carriers, including perfluorocarbon emulsion, hemoglobin-based carrier, synthetic heme, and its polymer metal complexes, have attracted increasing attention due to their ability in dissolving and delivering oxygen. However, although most of the perfluorocarbon emulsion could not be applied as blood substitutes until now, their application in medicine is still continued because of their therapeutic effect, which would be used on potential clinical care, such as cancer diagnosis, organ transplantation, and prevention of ischemia/reperfusion injury of tissues and organs. For example, Jia et al reported perfluoropentane-encapsulated hollow mesoporous prussian blue nanocubes for activated ultrasound imaging and photothermal therapy of cancer. Marada et al used perfluorocarbon to improve post-transplant survival and early kidney function following prolonged cold ischemia. However, few reports have focused on the effect of oxygen in perfluorocarbon emulsion on the physiological characteristics of cell and/or organism during the therapy using perfluorocarbon emulsion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial oxygen carriers, including perfluorocarbon emulsion, hemoglobin-based carrier, synthetic heme, and its polymer metal complexes, have attracted increasing attention due to their ability in dissolving and delivering oxygen. However, although most of the perfluorocarbon emulsion could not be applied as blood substitutes until now, their application in medicine is still continued because of their therapeutic effect, which would be used on potential clinical care, such as cancer diagnosis, organ transplantation, and prevention of ischemia/reperfusion injury of tissues and organs. For example, Jia et al reported perfluoropentane-encapsulated hollow mesoporous prussian blue nanocubes for activated ultrasound imaging and photothermal therapy of cancer. Marada et al used perfluorocarbon to improve post-transplant survival and early kidney function following prolonged cold ischemia. However, few reports have focused on the effect of oxygen in perfluorocarbon emulsion on the physiological characteristics of cell and/or organism during the therapy using perfluorocarbon emulsion.…”
Section: Introductionmentioning
confidence: 99%
“…7−14 For example, Jia et al 7 reported perfluoropentane-encapsulated hollow mesoporous prussian blue nanocubes for activated ultrasound imaging and photothermal therapy of cancer. Marada et al 13 used perfluorocarbon to improve post-transplant survival and early kidney function following prolonged cold ischemia. However, few reports have focused on the effect of oxygen in perfluorocarbon emulsion on the physiological characteristics of cell and/or organism during the therapy using perfluorocarbon emulsion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The authors found increased expression of mRNA HO-1 and down regulation of mRNA iNOS after preservation. Furthermore, Marada et al recently demonstrated increased survival and improved renal function after preservation using the standard TLM (PFC+UW) again in rat kidneys [21]. …”
Section: Discussionmentioning
confidence: 99%
“…It was observed that posttransplant outcome with respect to one-month survival and creatinine levels was significantly improved compared to UWS storage. In addition, histological tissue damage and frequency of apoptosis were significantly reduced after TLM storage (Marada et al, 2010). In contrast, attempts to preserve porcine kidneys utilizing TLM resulted in increased inflammation, tissue injury and reduced renal function which raised the question whether TLM is suitable for organs from species larger than rodents (Hosgood and Nicholson, 2010).…”
Section: Tissue Oxygenation Prior To Solid Organ Transplantationmentioning
confidence: 99%